Calculation of electron-impact ionization of potassium - Bray, Igor; Fursa, Dmitry; Stelbovics, Andris (Institute of Physics Publishing Ltd., 2009)
We calculate electron-impact ionization of potassium at a broad range of energies for the case where it is the valence electron that is ejected. The convergent close-coupling method is used to calculate the total and fully differential cross sections. The unusual shape of the total ionization spin asymmetries measured by Baum et al. [1] is explained. However, agreement with the fully differential cross section measurements of Murray [2] is somewhat mixed.